The Influence of Work-Life Balance and Perceived Organizational Support on Employee Engagement Mediated by Psychological Well-Being - PRATIWI, Audy Ratih; NUSANDARI, Arum Wardhani; DEWI, Rusmalia (International Journal of Environmental, Sustainability, and Social Science, 2025)
This study aims to determine the effect of work-life balance and organizational perception on employee engagement through psychological well-being among members of the Central Java Regional Police Traffic Directorate. The research method used is quantitative, with a population of 332 respondents. For sampling, the researcher employed purposive sampling, resulting in a sample of 120 respondents who met the criteria. Data collection was conducted using a scale method comprising the Work-Life Balance Scale, Perceived Organization Scale, Employee Engagement Scale, and Psychological Well-Being Scale. Furthermore, the analysis method used in this study was Structural Equation Modeling (SEM) using the SmartPLS 4.0 application. The results obtained in this study indicate that work-life balance affects employee engagement (T Statistic= 2.753; P=0.000), perceived organization also affects employee engagement (T Statistic=5.055; P=0.000), Psychological Well-Being influences Employee Engagement (T Statistic=5.131; P=0.000), Work-Life Balance influences Psychological Well-Being (T Statistic=4.477; P=0.000), Psychological Well-Being influences Employee Engagement (T Statistic=3.138; P=0.002), furthermore, Work-Life Balance influences Employee Engagement through Psychological Well-Being (T Statistic=1.998; P=0.031), while Perceived Organization does not influence Employee Engagement through Psychological Well-Being (T Statistic=1.693; P=0.091).